2018
DOI: 10.1108/et-08-2017-0124
|View full text |Cite
|
Sign up to set email alerts
|

Venturing under fire

Abstract: Purpose The purpose of this paper is to examine how a new entrepreneurship education (EE) intervention offered at conflict-ridden Maiduguri, Nigeria, is having transformative impacts through new venture creation and poverty reduction. Design/methodology/approach The paper adopts a single case study approach, drawing from in-depth interviews of participants, experts, and facilitators of the entrepreneurship training, in addition to relevant memos and documents. Findings The findings indicate that the EE pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
(69 reference statements)
0
15
0
Order By: Relevance
“…Poverty Reeducation: It describes a reduction in citizen's poverty through CPEC. We used mixed items (e.g., adopted from [6,52] as well as self-developed items to measure poverty reduction through CPEC.…”
Section: Measurement Of the Variablesmentioning
confidence: 99%
“…Poverty Reeducation: It describes a reduction in citizen's poverty through CPEC. We used mixed items (e.g., adopted from [6,52] as well as self-developed items to measure poverty reduction through CPEC.…”
Section: Measurement Of the Variablesmentioning
confidence: 99%
“…According to Honing (2004), a lot of researchers indicated that there is a luck of studies determining EE effectiveness and outcomes. Entrepreneurship education research has received much attention recently based on the benefits that it can bring to individuals and Theory Reference Total Theory of planned behavior Ahmed et al (2017), Bandera et al (2018), Carvalho et al (2015), Iwu et al (2019), Kariv et al (2018), Kolade (2018), Mamun et al (2017), Michelle andTendai (2017), Nowi nski et al (2017), Otache (2019a, b), Shinnar et al (2014), Testa andFrascheri (2015), von Graevenitz et al (2010), Walter and Dohse (2012) 14 Social learning theory Carvalho et al (2015), Dou et al (2019), Gonz alez-Serrano et al Rideout and Gray (2013) have stated that entrepreneurship education suffers from the lack of a coherent conceptual research framework that is comprehensively grounded on the knowledge of general education and the philosophy of entrepreneurship education. In relation to this point, very few of sample studies were based on a mixed-methodology approach.…”
Section: Research Methodology Distributionmentioning
confidence: 99%
“…In stable political environments, farmers have access to support services, including extension services and training programs, which are essential for the successful implementation of new technologies (De Clercq et al, 2018). On the other hand, in conflict-ridden areas, these services may not be available, reducing the effectiveness of technology adoption (Kolade, 2018). Furthermore, in such environments, farmers may not be able to access the necessary inputs, such as seed and fertilizer, which are critical to the success of new farming methods (Kolade, 2018).…”
Section: Factors Related To Political Stabilitymentioning
confidence: 99%
“…On the other hand, in conflict-ridden areas, these services may not be available, reducing the effectiveness of technology adoption (Kolade, 2018). Furthermore, in such environments, farmers may not be able to access the necessary inputs, such as seed and fertilizer, which are critical to the success of new farming methods (Kolade, 2018).…”
Section: Factors Related To Political Stabilitymentioning
confidence: 99%